Mesoporous carbonated hydroxyapatite/chitosan porous materials for removal of Pb(ii) ions under flow conditions. Issue 115 (7th December 2016) - Wen, Xi; Shao, Chun-Tao; Chen, Wei; Lei, Yong; Ke, Qin-Fei; Guo, Ya-Ping
Abstract : Mesoporous carbonated hydroxyapatite/chitosan porous materials are fabricated for the first time, which show good adsorption properties for Pb(ii ) ions even under flow conditions. Abstract : Pb(ii ) ions are highly harmful to the environment and human health because of their bioaccumulation, non-degradability and toxicity. Herein, we fabricated mesoporous carbonated hydroxyapatite (HAP)/chitosan (CS) porous materials (MHCMs) by using calcium carbonate/CS porous materials (CCPMs) as precursors. After soaking in phosphate buffer solution (PBS), the CaCO3 particles in the CCPMs were converted to carbonated HAP plates with a preferred c -plane orientation via a dissolution–precipitation reaction. The MHCMs possessed interconnected macropores with pore sizes of 50–150 μm and mesopores with pore sizes of 3.97 nm, which caused them to have a great BET surface area of 111.3 m 2 g −1 and a pore volume of 0.199 cm 3 g −1 . The sorption performance of the MHCMs for Pb(ii ) ions was evaluated by the flow of 400 mg L −1 lead solutions through the adsorbents, and HAP/CS porous materials (HCPMs) served as control samples. After adsorbing Pb(ii ) ions, the HAP particles in both the MHCMs and HCPMs were transferred into lead hydroxyapatite (PbHAP) rods. At the adsorption equilibrium, the adsorption amounts of the MHCMs and HCPMs arrived at 559.6 and 264.4 mg g −1, respectively. The MHCMs had better adsorption properties than the HCPMs because of their large surface area, hierarchically porous structures, low Ca/P ratio, good degradability and plate-like carbonated HAP with a preferred c -plane orientation. The adsorption of Pb(ii ) ions on MHCMs exhibited higher compliance with the pseudo-second-order kinetic model than the pseudo-first-order kinetic model, suggesting that the adsorption process was mainly controlled by chemical adsorption for Pb(ii ) ions. Therefore, the MHCMs have great potential for the removal of Pb(ii ) ions from aqueous solutions even under flow conditions.